Assessment of sex in a modern Turkish population using cranial anthropometric parameters. (July 2016) - Ekizoglu, Oguzhan; Hocaoglu, Elif; Inci, Ercan; Can, Ismail Ozgur; Solmaz, Dilek; Aksoy, Sema; Buran, Cudi Ferat; Sayin, Ibrahim
Graphical abstract: Highlights: CT analysis of the cranium is a suitable tool for assessment of sex. The most dimorphic structure was the bizygomatic diameter. 87.5% of females and 87.0% of males were classified accurately by function 2. Abstract: The utilization of radiological imaging methods in anthropometric studies is being expanded by the application of modern imaging methods, leading to a decrease in costs, a decrease in the time required for analysis and the ability to create three-dimensional images. This retrospective study investigated 400 patients within the 18–45-years age group (mean age: 30.7 ± 11.2 years) using cranial computed tomography images. We measured 14 anthropometric parameters (basion-bregma height, basion-prosthion length, maximum cranial length and cranial base lengths, maximum cranial breadth, bizygomatic diameter, upper facial breadth, bimastoid diameter, orbital breadth, orbital length, biorbital breadth, interorbital breadth, foramen magnum breadth and foramen magnum length) of cranial measurements. The intra- and inter-observer repeatability and consistency were good. From the results of logistic regression analysis using morphometric measurements, the most conspicuous measurements in terms of dimorphism were maximum cranial length, bizygomatic diameter, basion-bregma height, and cranial base length. The most dimorphic structure was the bizygomatic diameter with an accuracy rate of 83% in females and 77% in males. In this study, 87.5% of females and 87.0% of males were classified accurately by this model including four parameters with a sensitivity of 91.5% and specificity of 85.0%. In conclusion, CT cranial morphometric analysis may be reliable for the assessment of sex in the Turkish population and is recommended for comparison of data of modern populations with those of former populations. Additionally, cranial morphometric data that we obtained from modern Turkish population may reveal population specific data, which may help current criminal investigations and identification of disaster victims.